2006
DOI: 10.1070/qe2006v036n12abeh013262
|View full text |Cite
|
Sign up to set email alerts
|

Opto-acoustic diagnostics of the thermal action of high-intensity focused ultrasound on biological tissues: the possibility of its applications and model experiments

Abstract: View the article online for updates and enhancements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 19 publications
5
38
0
Order By: Relevance
“…A study from Nilsson et al (1998) demonstrated 100% to 300% increase in optical absorption and 120% to 280% increase in reduced scattering coefficient (for 600-1500 nm) in necrotic and normal rat liver in vivo. Similar trends were reported for ex vivo porcine liver (Khokhlova et al 2006) and chicken breast (Ben-David et al 2008) at wavelengths of 1064 and 1041 nm, respectively. Three major mechanisms have been proposed for the observed increases in optical absorption and scattering.…”
Section: Acousto-optic Imaging (Aoi)supporting
confidence: 85%
“…A study from Nilsson et al (1998) demonstrated 100% to 300% increase in optical absorption and 120% to 280% increase in reduced scattering coefficient (for 600-1500 nm) in necrotic and normal rat liver in vivo. Similar trends were reported for ex vivo porcine liver (Khokhlova et al 2006) and chicken breast (Ben-David et al 2008) at wavelengths of 1064 and 1041 nm, respectively. Three major mechanisms have been proposed for the observed increases in optical absorption and scattering.…”
Section: Acousto-optic Imaging (Aoi)supporting
confidence: 85%
“…This is consistent with the changes in optical properties of soft tissues reported in the literature. 1,21,37 In the experimental results given in Fig. 8, the normalized change in AO signal magnitude DS n was observed to be highly correlated with lesion volume under a wide variety of exposure conditions, with DS n increasing monotonically with lesion volume.…”
Section: Hifu Monitoringmentioning
confidence: 82%
“…Moreover, the optical properties of tissue have been shown to vary markedly in between normal and necrotic tissues, with necrotic tissue showing increased absorption and scattering and the specific increase dependent on tissue type. 1,21,37 The HIFU monitoring results demonstrate that real-time monitoring of lesion formation and growth is possible using AOI combined with lock-in detection.…”
Section: Hifu Monitoringmentioning
confidence: 95%
“…The increase in the amplitude of photoacoustic signals after HIFU treatment is consistent with previous results. 16,17 The increase in the amplitude of photoacoustic signals after HIFU can be attributed to a combination of several factors. Notably, the Grüneisen parameter is affected by tissue coagulation.…”
Section: Methodsmentioning
confidence: 99%
“…15 PAI has demonstrated to be capable of monitoring thermal lesions generated by HIFU or other means. 16,17 A study for PAI guidance of HIFU has also been proposed with the application of a time-reversal technique. 18 Currently, PAI and HIFU are performed by two separate systems.…”
Section: Introductionmentioning
confidence: 99%